2020
DOI: 10.1111/jrh.12417
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical and Anesthesia Workforce and Provision of Surgical Services in Rural Communities: A Mixed‐Methods Examination

Abstract: Purpose: Rural-urban disparities in the surgical and anesthesia workforce exist. This mixed-methods study describes the distribution of the surgical and anesthesia workforce and qualitatively explores how such workforce and other factors influence rural hospitals' provision of surgical services. Methods: We calculated provider counts by county from the Area Health Resource File. Using American Hospital Association survey data, we sampled rural hospitals, stratified by critical access status and state policies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…However, other factors ultimately appear to predict the likelihood of hospitals providing CRNA services. 8 In addition to examining the opt-out policy's effect on the likelihood of hospitals providing CRNA services, here we also highlight the aforementioned county and organization level factors examined. While the opt-out results are not necessarily intuitive, other factors line up with what could be reasonably expected a priori.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other factors ultimately appear to predict the likelihood of hospitals providing CRNA services. 8 In addition to examining the opt-out policy's effect on the likelihood of hospitals providing CRNA services, here we also highlight the aforementioned county and organization level factors examined. While the opt-out results are not necessarily intuitive, other factors line up with what could be reasonably expected a priori.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research suggests that opt-out policy adoption is a function of physician power or the relative power of CRNAs in a state. 2 It appears that more has to change than simply adopting an opt-out policy, 7,8 as opting out is potentially just a show of action decoupled from practice in reality. For one, increasing hospital CRNA provision will likely require addressing facility SOPs, a topic that could be addressed in future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comfort care model, as a new type of medical care, has played an important role in various clinical diseases, such as postpartum care of parturients [ 19 ], care of patients with advanced cancer [ 20 ], and perioperative care of various diseases [ 21 , 22 ]. Among them, respiratory department diagnosis and treatment is particularly important for comfort care models due to the wide range of populations faced, especially for children.…”
Section: Discussionmentioning
confidence: 99%
“… 16 In 2020, Cohen and colleagues found that among rural counties with at least a short-term general hospital, 50.8% were without a general surgeon, and slightly more, 52.2%, were without any surgical specialists. 21 Although these studies do not offer an apples-to-apples comparison, taken together they imply a dire situation in 2020, with one-half of all rural counties having no surgical services.…”
Section: Surgery As An Economic Engine In Rural America: Where Are We?mentioning
confidence: 99%